Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
[tex](-3, -3), \ \ (6, 12)\\ \\distance \ formula : \\ \\d =\sqrt{(x_{2}-x_{1})^2 +(y_{2}-y_{1})^2} \\ \\d =\sqrt{(6-(-3))^2 +(12-(-3) )^2} =\sqrt{(6+3)^2 +(12+3 )^2} =\sqrt{9^2+15^2}=\\ \\=\sqrt{81+225}=\sqrt{306}=\sqrt{9\cdot 34}=3\sqrt{34}=3\cdot 5.83= 17.49[/tex]
[tex]A=(x_A;y_A)\ \ \ and\ \ \ B=(x_B;y_B)\\\\ \Rightarrow\ \ \ |AB|= \sqrt{(x_A-x_B)^2+(y_A-y_B)^2} \\----------------------\\\\A=(-3;-3);\ \ \ B=(6;12)\\\\|AB|= \sqrt{(-3-6)^2+(-3-12)^2} =\\\\.\ \ \ \ \ \ = \sqrt{81+225} = \sqrt{306} =3 \sqrt{34} \approx17.49[/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.